2017
DOI: 10.1021/acs.inorgchem.7b01895
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrochemical Consequences of [Cp*] Ligand Protonation

Abstract: There are few examples of the isolation of analogous metal complexes bearing [η-Cp*] and [η-Cp*H] (Cp* = pentamethylcyclopentadienyl) complexes within the same metal/ligand framework, despite the relevance of such structures to catalytic applications. Recently, protonation of Cp*Rh(bpy) (bpy = 2,2'-bipyridyl) has been shown to yield a complex bearing the uncommon [η-Cp*H] ligand, rather than generating a [Rh-H] complex. We now report the purification and isolation of this protonated species, as well as charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
82
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 43 publications
(73 reference statements)
6
82
1
Order By: Relevance
“…of acid results in transfer of the proton to the [Cp*] ring, resulting in a new rhodium(I) species bearing endo η 4 ‐pentamethylcyclopentadiene as a ligand. Our newest experiments have shown that this [(Cp*H)Rh] complex is isolable in pure form and stable in solution on a timescale of minutes to hours . Importantly, this compound is competent for H 2 evolution upon addition of a second equivalent of acid.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations
“…of acid results in transfer of the proton to the [Cp*] ring, resulting in a new rhodium(I) species bearing endo η 4 ‐pentamethylcyclopentadiene as a ligand. Our newest experiments have shown that this [(Cp*H)Rh] complex is isolable in pure form and stable in solution on a timescale of minutes to hours . Importantly, this compound is competent for H 2 evolution upon addition of a second equivalent of acid.…”
Section: Introductionmentioning
confidence: 72%
“…The 1 H NMR spectrum revealed a new set of bipyridine signals in the aromatic region with resonances at 9.23 ppm (d, 3 J H,H =5.5 Hz, 2 H), 8.77 ppm (s, 2 H), and 8.00 ppm (d, 3 J H,H =5.5 Hz, 2 H) as well as a doublet at 0.55 ppm (d, 4 J H,H =6.2 Hz, 3 H) (see Supporting Information). This spectrum is highly reminiscent of (Cp*H)Rh(bpy)Br, a known intermediate in H 2 evolution with 2 , and recently synthesized and isolated at preparative scale by our group …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5,13] Theb and at 440 nm is due to metal-to-ligand charge-transfer (MLCT) transitions from the Ru II center to both the tpphz and the tbbpy ligands ( Figure 2B). [14] Further evidence is pro- Thes ame was observed for the photochemical reduction of Ru(tpphz)RhCp* in presence of TEA ( Figure S17).…”
Section: Introductionmentioning
confidence: 77%